1996
DOI: 10.1038/383272a0
|View full text |Cite
|
Sign up to set email alerts
|

A new serine-protease fold revealed by the crystal structure of human cytomegalovirus protease

Abstract: Human cytomegalovirus (hCMV), a herpesvirus, infects up to 70% of the general population in the United States and can cause morbidity and mortality in immunosuppressed individuals (organ-transplant recipients and AIDS patients) and congenitally infected newborns. hCMV protease is essential for the production of mature infectious virions, as it performs proteolytic processing near the carboxy terminus (M-site) of the viral assembly protein precursor. hCMV protease is a serine protease, although it has little ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
127
2

Year Published

1997
1997
2011
2011

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 162 publications
(131 citation statements)
references
References 19 publications
2
127
2
Order By: Relevance
“…It has also been suggested that without R-site cleavage, conformation of the pPR sequence destined to form the carboxyl terminus of assemblin would be different (14) and possibly unable to participate in the interactions and changes, which accompany dimerization and activation. Thus, one explanation of our finding is that imidazole rescue of I-site cleavage works only when the active site residues are in the relative orientation they assume in the activated assemblin dimer, which may be different in the precursor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been suggested that without R-site cleavage, conformation of the pPR sequence destined to form the carboxyl terminus of assemblin would be different (14) and possibly unable to participate in the interactions and changes, which accompany dimerization and activation. Thus, one explanation of our finding is that imidazole rescue of I-site cleavage works only when the active site residues are in the relative orientation they assume in the activated assemblin dimer, which may be different in the precursor.…”
Section: Discussionmentioning
confidence: 99%
“…The crystal structure of assemblin places the I site within an unstructured loop in the vicinity of the active site (11)(12)(13)(14). Extension of the loop toward the interior of the protease would situate the I site in proximity to the catalytic residues.…”
Section: Discussionmentioning
confidence: 99%
“…This could lead to a tighter packing of the protease molecules. Second, sodium sulfate caused a small change in the organization of the HCMV protease dimer in these crystals (Tong et al, 1996). This might also have an impact on the crystal packing, as evidenced by the fact that crystal form D has the shortest c-axis length.…”
Section: Discussionmentioning
confidence: 99%
“…The amino-acid sequences of herpesvirus proteases have no detectable homology to other serine proteases or hydrolases. The crystal structure of HCMV protease has recently been determined in our laboratory by the seleno-methionyl multiple-wavelength anomalous diffraction (MAD) technique (Tong et al, 1996), and in other laboratories by the heavy-atom isomorphous replacement technique (Qiu et al, 1996;Shieh et al, 1996;Chen et al, 1996). It showed that HCMV protease possesses a new polypeptide backbone fold; confirmed that Ser132 and His63 are in close proximity in space; and identified His157 as the possible third member of the catalytic triad.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation